Credibility assessment of patient-specific biomechanical models to investigate proximal junctional failure in clinical cases with adult spine deformity using ASME V&V40 standard. Issue 5 (4th April 2022) - Lopez Poncelas, M.; La Barbera, L.; Rawlinson, J. J.; Crandall, D.; Aubin, C. E.
Abstract: Computational models are increasingly used to assess spine biomechanics and support surgical planning. However, varying levels of model verification and validation, along with characterization of uncertainty effects limit the level of confidence in their predictive potential. The objective was to assess the credibility of an adult spine deformity instrumentation model for proximal junction failure (PJF) analysis using the ASME V&V40:2018 framework. To assess model applicability, the surgery, erected posture, and flexion movement of actual clinical cases were simulated. The loads corresponding to PJF indicators for a group of asymptomatic patients and a group of PJF patients were compared. Model consistency was demonstrated by finding PJF indicators significantly higher for the simulated PJF vs. asymptomatic patients. A detailed sensitivity analysis and uncertainty quantification were performed to further establish the model credibility.